Differential, dominant activation and inhibition of notch signalling and APP cleavage by truncations of PSEN1 in human disease deficits - Newman, M.; Wilson, L.; Verdile, Giuseppe; Lim, A.; Khan, I.; Moussavi Nik, S.; Pursglove, S.; Chapman, G.; Martins, R.; Lardelli, M. (Oxford University Press, 2014)
PRESENILIN1 (PSEN1) is the major locus for mutations causing familial Alzheimer's disease (FAD) and is also mutated in Pick disease of brain, familial acne inversa and dilated cardiomyopathy. It is a critical facilitator of Notch signalling and many other signalling pathways and protein cleavage events including production of the Amyloidβ (Aβ) peptide from the AMYLOID BETA A4 PRECURSOR PROTEIN (APP). We previously reported that interference with splicing of transcripts of the zebrafish orthologue of PSEN1 creates dominant negative effects on Notch signalling. Here, we extend this work to show that various truncations of human PSEN1 (or zebrafish Psen1) protein have starkly differential effects on Notch signalling and cleavage of zebrafish Appa (a paralogue of human APP). Different truncations can suppress or stimulate Notch signalling but not Appa cleavage and vice versa. The G183V mutation possibly causing Pick disease causes production of aberrant transcripts truncating the open reading frame after exon 5 sequence. We show that the truncated protein potentially translated from these transcripts avidly incorporates into very stable Psen1-dependent higher molecular weight complexes and suppresses cleavage of Appa but not Notch signalling. In contrast, the truncated protein potentially produced by the P242LfsX11 acne inversa mutation has no effect on Appa cleavage but, unexpectedly, enhances Notch signalling. Our results suggest novel hypotheses for the pathological mechanisms underlying these diseases and illustrate the importance of investigating the function of dominant mutations at physiologically relevant expression levels and in the normally heterozygous state in which they cause human disease rather than in isolation from healthy alleles.